Kode Pembacaan dalam Cerpen Ngantosang Ulungan Bulan Kajian Semiotika - Tisna, Ayu Yuliani; Cika, I Wayan; Suardiana, I Wayan (Humanis, 2025)
The short story Ngantosang Ulungan Bulan by Carma Mira reflects Balinese culture within the context of social life and romance, particularly related to the custom that forbids a younger sibling from marrying before the elder. The main character experiences inner conflict because both of the older siblings remain unmarried for their own reasons. This story emphasizes the importance of preserving Balinese cultural identity amid the current of social change and conveys a moral message about respect for family and tradition. This study aims to reveal the meanings contained in the story using Roland Barthes' semiotic approach. The analysis is conducted through five main codes: hermeneutic, connotative, symbolic, action, and cultural. Through this approach, cultural values, traditional symbols, and the tension between modernity and custom can be explored. As a literary work written in the Balinese language, the story also demonstrates the importance of regional language as a medium for cultural preservation and the expression of community identity.